Handbook of human factors and ergonomics - Salvendy, Gavriel, 1938- (Hoboken, NJ : Wiley, 2012)
"This is the fourth edition of the market-leading reference for human factors and ergonomics researchers, academics, and professionals. Editor Gavriel Salvendy, a well-known and respected authority, has assembled the top thinkers and practitioners from throughout the world to update this volume. It features new coverage of voice communication, multi-modal design, human-robot communication, call center design and operation, design of electronic games, and much more.Plus new and expanded coverage of Human Error and Human Reliability Analysis"--
"This is the Fourth Edition of the market leading reference for human factors and ergonomics researchers, academics, and professionals. Well-known and respected authority, editor Gavriel Salvendy has assembled the top thinkers, and practitioners from throughout the world to update this volume. New coverage of voice communication; multi modal design; human-robot communication; call center design and operation; design of electronic games and much more"--
Machine generated contents note: I. The Human Factors Function1. A Discipline of Human Factors and Ergonomics Waldermar Karwowski2. Human Factors Engineering and Systems Design Sara J. Czaja and Sankaran N. NairII. The Human Factors Fundamentals3. Sensation and Perception Robert W. Proctor and Janet D. Proctor4. Selection and Control of Action Robert W. Proctor and Kim-Phuong L. Vu5. Information Processing Christopher D. Wickens and C. Melody Carswell6. Cross-Cultural Design Tom Plocher, P.L. Patrick Rau and Yee-Yin Choong7. Decision-Making Models, Decision Support, and Problem Solving Mark R. Lehto, Fiona Nah and Ji Soo Yi8. Mental Workload and Situation Awareness Michael A. Vidulich and Pamela S. Tsang9. Social and Organizational Foundations of Ergonomics Alvaro D. Taveira and Michael J. Smith10. Human Factors and Ergonomic Methods Julie A. Jacko, Ji Soo Yi, Francois Sainfort and Molly McClellan11. Anthropometry for Product Design Kathleen M. Robinette12. Basic Biomechanics and Workstation Design William S. MarrasIII. Design of Tasks and Jobs13. Task Analysis: Why, What, and How Erik Hollnagel14. Task Design and Motivation Holger Luczak, Tanja Kabel, and Torsten Licht15. Job and Team Design Frederick P. Morgeson, Michael A. Campion and Patrick F. Bruning16. Personnel Recruitment, Selection, and Turnover Jerry W. Hedge, Walter C. Borman and Dan Ispas17. Design, Delivery, Evaluation and Transfer of Training Systems Chris W. Coultas, Rebecca Grossman and Eduardo Salas18. Human Factors in Organizational Design and Management Pascale Carayon, Peter Hoonakker and Michael J. Smith19. Situation Awareness Mica R. Endsley20. Affective Engineering and Design Martin G. Helander and Halimahtun M. KhalidIV. Equipment, Workplace, and Environmental Design21. Workplace Design Nicolas Marmaras and Dimitris Nathanael22. Vibration and Motion Michael J. Griffin23. Sound and Noise: Measurement and Design Guidance John G. Casali24. Illumination Peter R. BoyceV. Design for Health, Safety, and Comfort25. Occupational Health and Safety Management Mark R. Lehto, Dave R. Clark and Bradley T. Cook26. Human Error and Human Reliability Analysis Joseph Sharit27. Managing Low Back Disorder Risk in the Workplace William S. Marras28. Work-Related Upper Extremity Musculoskeletal Disorders David Rodrick, Waldemar Karwowski and William S. Marras29. Warnings and Hazard Communications Michael S. Wogalter, Kenneth R. Laughery Sr. and Christopher B. Mayhorn30. Use of Personal Protective Equipment in the Workplace Grazyna Bartkowiak, Krzysztof Baszczynski, Anna Bogdan, Agnieszka Brochocka, Rafal Hrynyk, Emilia Irzmanska, Danuta Koradecka, Katarzyna Majchrzycka, Krzysztof Makowski, Anna Marscalek, Grzegorz Owczarek and Jan Zera31. Human Space Flight Barbara Woolford and Frances MountVI. Performance Modeling32. Modeling Human Performance in Complex Systems K. Ronald Laughery, Jr., Beth Plott, Michael Matessa, Susan Archer and Christian Lebiere33. Mathematical Models in Engineering Psychology: Optimizing Performance Donald L. Fisher, Richard Schweickert, and Colin G. Drury34. Human Supervisory Control Thomas B. Sheridan35. Human Digital Modeling in Design Vincent G. Duffy .
Includes index.
Keywords: Human engineering -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Industrial Engineering; ergonomija